Determinants of incident vertebral fracture in men and women: results from the European Prospective Osteoporosis Study (EPOS). - Roy, D; O'Neill, T; Finn, J; Lunt, M; Silman, A; Felsenberg, D; Armbrecht, G; Banzer, D; Benevolenskaya, L; Bhalla, A; Bruges Armas, J; Cannata, J; et al. (2003)
The aim of this analysis was to determine the influence of lifestyle, anthropometric and reproductive factors on the subsequent risk of incident vertebral fracture in men and women aged 50-79 years. Subjects were recruited from population registers from 28 centers across Europe. At baseline, they completed an interviewer-administered questionnaire and had lateral thoraco-lumbar spine radiographs performed. Repeat spinal radiographs were performed a mean of 3.8 years later. Incident vertebral fractures were defined morphometrically and also qualitatively by an experienced radiologist. Poisson regression was used to determine the influence of the baseline risk factor variables on the occurrence of incident vertebral fracture. A total of 3173 men (mean age 63.1 years) and 3402 women (mean age 62.2 years) contributed data to the analysis. In total there were 193 incident morphometric and 224 qualitative fractures. In women, an age at menarche 16 years or older was associated with an increased risk of vertebral fracture (RR = 1.80; 95%CI 1.24, 2.63), whilst use of hormonal replacement was protective (RR = 0.58; 95%CI 0.34, 0.99). None of the lifestyle factors studied including smoking, alcohol intake, physical activity or milk consumption showed any consistent associations with incident vertebral fracture. In men and women, increasing body weight and body mass index were associated with a reduced risk of vertebral fracture though, apart from body mass index in men, the confidence intervals embraced unity. For most variables the strengths of the associations observed were similar using the qualitative and morphometric approaches to fracture definition. In conclusion our data suggest that modification of other lifestyle risk factors is unlikely to have a major impact on the population occurrence of vertebral fractures. The important biological mechanisms underlying vertebral fracture risk need to be explored using new investigational strategies.